Psychometric properties for the General Procrastination Scale (GPS) Brazilian version - Chirinéa, Guilherme; Gonçalves, André Pereira; Lima, Villena Louise Meira Costa; Santos, Ana Luísa Menezes; Almeida, Cecília Pires de; Lodha, Pragya (Estudos de Psicologia (Campinas), 2025)
Abstract Objective Procrastination has been the subject of studies due to its impact on people’s lives, work performance, satisfaction, and mental health. Measuring this construct is necessary to understand daily life’s direct and indirect effects. The objective of this study was to verify the evidence of validity and reliability of the General Procrastination Scale for the Brazilian context as a method of investigating the phenomenon. Method Data were collected from 421 adults, aged between 18 and 64 years and with complete primary education, based on the application of a self-report measurement questionnaire. Results The results indicated a unifactorial structure and expected correlations with the external measures. Conclusion These results demonstrate the suitability of the scale for measuring procrastination in a Brazilian sample, which places this scale as a possibility of use in research to measure this construct. Resumo Objetivo A procrastinação tem sido alvo de estudos devido ao impacto que traz na vida das pessoas, rendimento no trabalho, satisfação e na saúde mental. Mensurar este construto é necessário para compreender os impactos diretos e indiretos no cotidiano. O objetivo deste estudo foi verificar as evidências de validade e fidedignidade da General Procrastination Scale para o contexto brasileiro como método de investigação do fenômeno. Método Foi realizada uma coleta de dados em 421 adultos, com idades entre 18 e 64 anos e ensino fundamental completo, a partir da aplicação de um questionário de medida de autorrelato. Resultados Os resultados indicaram estrutura unifatorial e correlações esperadas com as medidas externas. Conclusão Estes resultados indicam adequação da escala para mensuração da procrastinação em uma amostra brasileira, o que coloca esta escala como uma possibilidade de uso em pesquisas para mensuração deste construto.